2007
DOI: 10.1002/chir.20430
|View full text |Cite
|
Sign up to set email alerts
|

Enantioseparation using urea‐ and imide‐bearing chitosan phenylcarbamate derivatives as chiral stationary phases for high‐performance liquid chromatography

Abstract: Completely deacetylated chitosan was prepared by the treatment of commercial chitosan with 50% aqueous NaOH, and then derivatized into several new chitosan phenylcarbamate derivatives having a urea and an imide moiety at the 2-position of the glucosamine ring by the reaction with isocyanate and phthalic anhydride/isocyanate, respectively. The chitosan derivatives were coated on macroporous silica gel and evaluated as chiral stationary phases (CSPs) for high-performance liquid chromatography. The chiral recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…The similar trends could also be found for the chitosan derivatives [22,25]. As shown in Table 1 and Figs.…”
Section: Influence Of the Substituent Group On The Phenyl Moieties Ofsupporting
confidence: 84%
See 1 more Smart Citation
“…The similar trends could also be found for the chitosan derivatives [22,25]. As shown in Table 1 and Figs.…”
Section: Influence Of the Substituent Group On The Phenyl Moieties Ofsupporting
confidence: 84%
“…The lower solubility of chiral selectors is very important for the coated-type CSPs of polysaccharide derivatives, because these CSPs can work in a wider range of mobile phases, in which better enantioseparations may be gained. To date, there is still only a few studies and much less attention has been paid on chitosan derivatives based CSPs [23][24][25][26][27][28][29][30][31]. Meanwhile, most of the common coated-type CSPs exhibited poor solvent resistance in some organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been used as a starting material in the preparation of chiral selectors [5][6][7][8][9]. In 2008, Yamamoto et al [10] synthesized chitosan-urea and -imide phenylcarbamate derivatives and coated them onto a 7 lm macroporous silica gel pretreated with 3-aminopropyltriethoxysilane. It is interesting to note that these chitosan derivatives exhibited optical resolutions that were equal to or higher than those of cellulose or amylose derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…All optimized structures were subjected to vibrational frequency analysis. 6,19 The optimized structures were shown by software Gauss View (3.07).…”
Section: Methodsmentioning
confidence: 99%
“…With the development of lift science and diversification of research methods, the gas-phase chemistry about the compounds containing urea group is becoming a very attractive field. [4][5][6] Electrospray ionization tandem mass spectrometry (ESI-MS/MS) with both positive and negative ion modes, 7 as the ionization technology, was applied to investigating the gas-phase chemistries of compound 1, by transferring the preformed ions directly from solution to the gas-phase and studying its unimolecular transformations in the solvent-free conditions. 8 Our studies showed some general gas-phase chemistries of 2-pyrimidinyloxy-N-arylbenzylamines, such as intramolecular S N 2 reaction and Smiles rearrangement processes reported previously.…”
Section: Introductionmentioning
confidence: 99%